Urban governance and rapid urbanization issues in Malaysia - Ho, Chin Siong (Faculty of Built Environment, UTM, 2008)
The foundation of the present modern urban system in Malaysia was laid during British colonialism (1786-1957). During the colonial era, basic infrastructure such as transportation and utilities were built to support commercial, financial, social and administrative functions to further exploit the resources (e.g. tin and rubber) in the country. After Independence in 1957, the rate of urbanization in Malaysia is on the increase, from about 25% in 1960 to 65% in 2005 and is expected to exceed 70% by 2020. The government has taken innovative urban governance to achieve regional balance and prevention of primate cities by policies of decentralisation.